2021
DOI: 10.1029/2020ja028317
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of F‐Region Bottom‐Type Echoing Layer Over Gadanki

Abstract: Bottom‐type echoing layers observed from Gadanki are presented and analyzed. The analysis is based on observations made using a substantial database of the 30 MHz Gadanki Ionospheric Radar Interferometer (GIRI) during 2017–2019, collocated digisonde observations, and a few days of overlapping volume observations made using the GIRI and the 53 MHz Advanced Indian MST Radar (AIR) . The echoes commence well before the E‐ and F‐region sunsets and last as late as 23:00 Local Time. The echoing layers occur in the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Moreover, the statistical study by Hu et al. (2020) found no relationship between occurrences of BLSs and plasma plumes over Sanya (here note that the Sanya is very near the Fuke; besides, the same result was also obtained by Pavan Chaitanya and Patra (2021) over Gadanki). This is why Li et al.…”
Section: Results and Analysessupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, the statistical study by Hu et al. (2020) found no relationship between occurrences of BLSs and plasma plumes over Sanya (here note that the Sanya is very near the Fuke; besides, the same result was also obtained by Pavan Chaitanya and Patra (2021) over Gadanki). This is why Li et al.…”
Section: Results and Analysessupporting
confidence: 69%
“…(2020) found that almost all the BLSs observed in Sanya appeared generally at the altitude range of 195–235 km during the descending phase of solar cycle (2015–2018 years). A similar statistical study conducted by Pavan Chaitanya and Patra (2021) found that BLSs over Gadanki, India during 2017–2019 years commenced well before sunset and lasted late as 23:30 LT in the height range of 220–300 km with a thickness of 10–15 km; the most interesting finding in their study is that the height of the observed BLSs over Gadanki agreed very well with the height of the F ‐region peak electron density, and only those early commencement of BLSs before sunset were found to be associated with low h′f (<250 km).…”
Section: Results and Analysesmentioning
confidence: 70%
“…The BSL was first observed by Jicamarca radar operated at magnetic equator (Woodman & La Hoz, 1976). Then based on observations from other instruments, the BSL was found in low latitude and other longitudes (Hu et al., 2020; Hysell et al., 2005, 2006; Li et al., 2017; Lyu et al., 2021; Patra et al., 2014; Pavan Chaitanya & Patra, 2021; Rodrigues et al., 2004; Takahashi et al., 2010). With the increase of research, its characteristics and corresponding mechanisms have gradually been revealed.…”
Section: Introductionmentioning
confidence: 96%
“…During the past several decades, compared to the high occurrence rate of F region echoes at night, some cases of daytime F region echoes were reported since the background conditions in the daytime F region with a larger field‐line‐integrated Pedersen conductivity and a smaller plasma density gradient at the bottom of F region are not conducive to the development of R‐T instability or Perkins instability (Chaitanya & Patra, 2021; Hu et al., 2020; Kelly, 2009; Xie et al., 2020). Woodman et al.…”
Section: Introductionmentioning
confidence: 99%